Goods Sector Analysis: Firm Value Impacted by Tax Strategies and Institutional Ownership: Analisis Sektor Barang: Strategi Pajak, Kepemilikan Institusional, dan Nilai Perusahaan - Rachmad Dwi Wicaksono; Heman Ernandi (Academia Open, 2022)
This study investigates the impact of tax planning, tax avoidance, and earnings management on firm value, with a focus on the moderating role of institutional ownership. The research is based on a sample of 75 Indonesian companies from the Goods Industry Sector, covering the period from 2017 to 2019. Purposive sampling was employed to select the sample of 25 companies each year. The secondary data was processed using SmartPLS and analyzed using Structural Equation Modeling. The findings reveal that tax planning and tax avoidance do not significantly influence firm value when moderated by institutional ownership. However, earnings management exhibits a significant relationship with firm value when moderated by institutional ownership. These results contribute to the understanding of the interplay between tax-related practices, firm value, and the influence of institutional ownership in the context of the Goods Industry Sector. The implications of these findings provide valuable insights for policymakers, regulators, and managers aiming to enhance the value of companies within this sector. Highlights: The impact of tax strategies: The study examines the effects of tax planning, tax avoidance, and earnings management on firm value in the goods industry sector. It explores how these strategies influence the financial performance of companies. The role of institutional ownership: The research investigates the moderating role of institutional ownership in the relationship between tax-related practices and firm value. It highlights the influence of institutional investors on company performance and decision-making. Implications for firm value: The findings provide valuable insights for policymakers, regulators, and managers in the goods industry sector. The study offers implications for enhancing firm value through effective tax planning, minimizing tax avoidance, and addressing the role of institutional ownership in driving financial performance. Keywords: Tax planning, Tax avoidance, Earnings management, Institutional ownership, Goods industry sector